Hypoxia/Reoxygenation modulates Oxidative Stress Level and Antioxidative Potential in Lung Mitochondria: Possible participation of P53 and NF-KB Target Proteins - Olga Gonchar; Irina Mankovska (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2017)
Background  and  objective: Hypoxia/reoxygenation  (H/R)  is  a  key  factor  in  the  pathogenesis of the most lung diseases  where exсessive  ROS  production and  prooxidant/antioxidant  imbalance greatly contribute to disease progression. We have used severe hypoxia in sessions of repeated H/R of different duration as  a model of lung  pathologic  states  to  investigate  mitochondrial  oxidative  stress  intensity, protein   expression/activity of antioxidant enzymes manganese-superoxide   dismutase (MnSOD), glutathione  peroxidase  (GPx),  and  antiapoptotic  Bcl-2  as  well  as  protein  expression  of  their  upstream regulators: p53 and nuclear factor- kappa B (NF-kB). Methods: A total 86 rats were divided into five experimental groups and subjected to H/R [5 cycles of  10  min  hypoxia  (5.5  %  O2  in  N2)  alternated  with  10  min  normoxia,  daily].  Eight  rats  from  each  group were sacrificed  on  1st  -,  3rd  -  day,  1st  and  2nd  -  week  time  points.  Oxidative  stress  biomarkers  (ROS formation,  lipid  peroxidation,  H2O2  production,  GSH/GSSG  ratio,  and  mitochondrial  aconitase  activity as marker of compartment-specific superoxide anion production), indices of antioxidant status (MnSOD,GPx,  glutathione  -S-transpherase  activities,  and  reduced  glutathione  level)  were  measured  in  lung mitochondria.  Western  blot  was  used  to  detect  the  protein  levels  of  p53,  Bcl-2,  MnSOD,  and  GPx  in mitochondria as well as the phosphorylated NF-kB p65 in the nucleus of lung cells. Expression of mRNA MnSOD was determined by real-time polymerase chain reaction. Results: The short- (1-3 days) and long-term (1-2 wk) H/R differentially affects the oxidative stress level,  p53  protein  expression  and  its  subcellular  distribution  as well as antioxidant  capacity  in  lung mitochondria.The  long-term  H/R  caused  mitochondrial  p53 protein  translocation, a decrease in Bcl-2 protein  content, and  a  significant  increase in nuclear  accumulation  of  the  phosphorylated  NF κB p65 protein. We observed  an  increase  in  GPx  protein  content/activity, in parallel  with  decrease  in  MnSOD protein  level  and  activity.  In  the dynamics of  MnSOD  gene expression  we  found  a  phase  time  point dependence. Conclusions:  Long  lasting  H/R  leads  to  mitochondrial  prooxidant/antioxidant  disbalance  that resulted  in  redox  alteration  as  consequence  of  oxidative  stress  propagation  and  apoptotic  cascade activation. A close correlation between mitochondrial p53 Protein level and protein expression/activities of  its  targets  MnSOD  and  GPx  suggest  participation  of  p53  in  regulation  of  H/R-induced  mitochondrial oxidative stress level.